Biomass production of four Cynara cardunculus clones and lignin composition analysis. (May 2015) - Lourenço, Ana; Neiva, Duarte Miranda; Gominho, Jorge; Curt, María Dolores; Fernández, Jesús; Marques, António Velez; Pereira, Helena
Abstract: Four Cynara cardunculus clones, two from Portugal and two from Spain were studied for biomass production and their lignin was characterized. The clones differed in biomass partitioning: Spanish clones produced more capitula (54.5% vs. 43.9%), and Portuguese clones more stalks (37.2% vs. 25.6%). The heating values (HHV0 ) of the stalks were similar, ranging from 17.1 to 18.4 MJ/kg. Lignin was studied by analytical pyrolysis (Py-GC/MS(FID)), separately in depithed stalks (stalksDP ) and pith. StalksDP had in average higher relative proportions of lignin derived compounds than pith (23.9% vs. 21.8%) with slightly different lignin monomeric composition: pith samples were richer in syringyl units as compared to stalksDP (64% vs. 53%), with S/G ratios of 2.1 and 1.3, respectively. The H:G:S composition was 7:40:53 in stalksDP and 7:29:64 in pith. The lignin content ranged from 18.8% to 25.5%, enabling a differentiation between clones and provenances. Highlights: Spanish and Portuguese cardoon clones differ in aboveground biomass partitioning. Cardoon lignin was characterized as a SG-lignin by Py-GC/MS(FID). Depithed stalks and pith differ in lignin content and composition. Pith has less lignin and a higher S/G ratio than depithed stalls.